(untitled) (Research, Society and Development, 2021)
Bipolar Mood Disorder (THB) is characterized by mood change, which can be euphoric or depressive, its intensity and symptoms vary from person to person. This disorder also affects both men and women. There are many taboos and prejudice with people who have THB which makes it difficult, in many cases, to go from patients to doctors for examinations and diagnosis. This research aimed to discuss about THB from the perspectives of common sense and psychopathology, using a bibliographic procedure research and qualitative approach. Data were collected on the Scielo and Capes scientific platforms. The study showed that, by common sense, the patient of THB can bring great risks to society, which sees him as a mental patient without control or cure, and it is necessary to keep these people from social life. The treatment is not widely publicized, causing a perpetuation of prejudice in relation to THB. The little information about the disorder and prejudiced attitudes, leads many patients to suffer from marginalization and during the depressive episode, in some cases, the suicide attempt. The great challenge of mental health professionals is to bring knowledge of the disorder to society, in order to reduce this stigma about THB.